Explorando la interacción entre el salario mínimo, el crecimiento económico, la calidad burocrática, la corrupción en el sector público y el desempleo juvenil en Ecuador durante 1991 a 2021: usando modelos ARDL y DYNARDL - Prieto Torres, Lolita Anahi (2024)
In Ecuador, young people without experience represent 46% of the percentage of youth unemployment, while young people with experience symbolize 56% of this economic and social phenomenon, being relatively high percentages, which reflect an enormous problem for Ecuadorian society. To this end, the general objective of this research is to evaluate the nexus between youth unemployment and minimum wage, economic growth, bureaucratic quality and corruption in the public sector through statistical and econometric techniques with the purpose of suggesting structural policies to mitigate youth unemployment in Ecuador. To determine the results of this research, some databases were used, such as: World Bank, CEPALSTAT and V- DEM, from these databases certain useful variables were extracted, these are: youth unemployment, minimum wage, economic growth, bureaucratic quality and corruption in the public sector in order to develop a methodology with econometric techniques for time series. From them, the results show a direct short-term relationship between youth unemployment and the minimum wage, that is, an increase of 1 dollar in the minimum wage causes an increase in youth unemployment. Establish links between the government and the private sector, in terms of programs aimed at young people, given that a large part of the jobs come from the “Mi primer empleo” program, by making this agreement the policy is expanded for those young people who are in both sectors.